2019
DOI: 10.1038/s41598-019-56268-3
|View full text |Cite
|
Sign up to set email alerts
|

Collagen fragments quantified in serum as measures of desmoplasia associate with survival outcome in patients with advanced pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) patients have poor prognosis and poor response to treatment. This is largely due to PDAC being associated with a dense and active stroma and tumor fibrosis (desmoplasia). Desmoplasia is characterized by excessive degradation and formation of the extracellular matrix (ECM) generating collagen fragments that are released into circulation. We evaluated the association of specific collagen fragments measured in pre-treatment serum with outcome in patients with PDAC. Matrix m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…It is worth noting that fibrillar collagens-derived proteolytic fragments are released in the blood stream where they represent easily accessible biomarkers to monitor cancer progression (140,(344)(345)(346).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that fibrillar collagens-derived proteolytic fragments are released in the blood stream where they represent easily accessible biomarkers to monitor cancer progression (140,(344)(345)(346).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that several collagen biomarkers have a diagnostic, prognostic and predictive capacity in various solid tumour types 9 , 20 , 34 43 . As an example, turnover products from collagen type III are augmented in serum from patients with ovarian, melanoma, pancreatic and breast cancer 20 – 23 , 36 , 39 , 41 , 42 . In addition, biomarkers from collagen type III have been shown to predict response to treatment in patients with metastatic pancreatic cancer 36 .…”
Section: Introductionmentioning
confidence: 99%
“… 13 The two collagen-derived biomarkers assess different components of the ECM in the tumor microenvironment (TME) by reflecting a dense stromal interstitial matrix and fibrotic activity (PRO-C3) and degradation of the basement membrane (C4M). 14 …”
Section: Introductionmentioning
confidence: 99%